Natural mycorrhizal colonization of citrus rootstocks under field conditions - Nunes, Maiara de Souza; Soares, Ana Cristina Fermino; Filho, Walter dos Santos Soares; Lêdo, Carlos Alberto da Silva (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the mycorrhizal colonization of citrus rootstocks (traditional and hybrid), in the field, selected as tolerant to water deficit by the Citrus Breeding Program of Embrapa Mandioca e Fruticultura Tropical. Fine roots and soil samples were collected in two seasons of the year. The mycorrhizal colonization was high in both citrus orchards sampled, and varied among the genotypes and the seasons of the year. All citrus rootstocks presented high percentages of root colonization, varying from 42 to 83%, even in high soil phosphorous conditions.
Keywords: hybrids; phosphorous; native mycorrhiza